Development of scholastic well-being in the course of the 5th grade in secondary education. (2022) - Obermeier, Ramona; Gläser-Zikuda, Michaela
Highlights: Longitudinal multilevel-models. Decrease in all dimensions of scholastic well-being in the course of the first year in secondary education. Gender differences in initial values and changes in several dimensions of scholastic well-being. Educational track as strongest influencing factor on positive attitudes towards school and scholastic self-concept. Lower social problems, physical complaints and worries of students in girls' schools. Abstract: Scholastic well-being is highly relevant, as it is connected with achievement and successful coping with critical life events. Since well-being in school is a multidimensional construct, it is necessary to analyze trajectories of these multiple dimensions to get a deeper understanding of changes and influencing factors. The empirical base for differential development of scholastic well-being for girls and boys, students with and without migration background and students attending medium and academic educational tracks is inconsistent. Additionally, there is a lack of findings regarding students' well-being in co-educational versus single-sex schools. Therefore, the current study aims at analyzing changes in all six dimensions of scholastic well-being during the 5th grade for specific groups of students (boys and girls, students with and without migration backgrounds, students attending medium and academic educational tracks and in co-educational versus single-sex schools). Based on a sample of N  = 1, 042 students in Catholic schools (80.5% female, 25.8% with migration background, 48.9% in a medium educational track, 54.3% in single-sex schools) who participated in three measurement time points, longitudinal multi-level analyses were calculated. Results reveal a decrease in all dimensions of scholastic well-being over time. Additionally, they illustrate the causal role of time-stable covariates, such as gender, educational track, migration background, and co-educational versus single-sex schooling. The results show slightly different trajectories for male and female students. Thus, the presented study builds upon results of previous studies by providing further information on short-term changes of scholastic well-being and different trajectories for specific groups of students.